Ultrasonography in Tubo-Ovarian Abscess: A Case Study - Muhamad Rafdhi; Ririn Angeline Limbong; Fransiska Ayu Septiani Pratama Putri; Daniel Riskiandi; Maxzillion Sky Kasnadi; Stefanie Sumartono; Apriani Lam; Syifa Navisah; Nadya Ariella; Mathias Rusli (Medical Clinical Update, 2022)
Tubo-ovarian abscess (TOA) is one of acute complications of pelvic inflammatory disease that usually occur in woman of childbearing age. Factors associated with TOA are reproductive age, Intra-Uterine Device (IUD) insertion, multiple sexual partners, and a history of a prior episode of PID. The classic presentation of a TOA includes abdominal pain, pelvic mass on examination, fever, and leukocytosis. However, prompt diagnostic evaluation must be undertaken to specify the diagnosis. Tubo-ovarian abscess can be found on imaging with ultrasonography, computed tomography (CT), or magnetic resonance imaging (MRI). Ultrasonography as the cheaper of all could be used as first-line diagnostic modality. This study presents an example of ultrasonography examination of 42-year-old woman presenting with stomach pain and fever. Abdominal ultrasonography was performed and we found abscess formation in adnexa. Emergency surgery was performed and antibiotics were given after surgery. This study showed us how abdominal ultrasound could diagnose tubo-ovarian abscess.